Nietzsche, Religion, and Mood - Saarinen, Sampsa Andrei (Monographien und Texte zur Nietzsche-Forschung, 2019)
This monograph casts new light on Nietzsche's philosophy of religion by examining the role of mood in the philosopher's critical project. The novel approach does not only contribute to scholarship on Nietzsche it also raises challenging questions for the interdisciplinary discourse on secularization. If there are moods intimately related to specific religions, are there also moods specific to forms of atheist experience?